Ibn Sina's Concept of Thought (Religious-Rational) About Education and Its Relevance to Contemporary Islamic Education - Nuril Fathiha; Eva Latipah; Sumedi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research was designed to find out the biography, thoughts of Ibn Sina, and the relevance of these thoughts to contemporary Islamic education in Indonesia. The research method used is the library research method which carries out literature studies through various sources of information. At the data analysis stage, the author uses a content analysis method which is useful for compiling and selecting data related to thoughts from various sources of information related to Ibn Sina's thoughts on education. The results obtained are that there is relevance in the aspect of educational goals and learning methods from the thoughts conveyed by Ibnu Sina with Contemporary Islamic Education in Indonesia. Where the educational objectives conveyed by Ibnu Sina are regarding the development of all aspects of students by paying attention to character, this is in accordance with the general educational objectives in Indonesia. Apart from that, the learning methods presented by Ibnu Sina have relevance in their application to learning methods in Islamic boarding schools in Indonesia.